ANALISIS PEMBAYARAN GAJI DAN UPAH TENAGA OPERATOR PADA PT. THIESS CONTRACTOR INDONESIADI SANGATTA - , SUYATIN, RIA AGUSTINE , ELFREDA A.LAU (EKONOMIA, 2015)
The objective is to determine the payment of salaries of employees PT.Thiess operator Contractor Indonesia.Rumusan matter whether Amountpayment of salaries and wages of employees at PT. Thiess Contractor Indonesia in accordance with the regulations Sangatta East Kalimantan Governor No. 561 / K.806 / 2013.Basic theory of Human Resource Management outlines the Definition of Management and Human Resources, Interest, Wages, Analysing Wage Wages method, the basic assessment Wage and Wage measurement. Hypothesis: Is the amount of salaries and wages of employees PT.Thiess Contractor Indonesia paid in accordance with the decision Gunernur or based PP.Menkeu No. 162 / PMK.011 / 2012 and the amount of non-taxable income.Based on data analysis, the minimum wage of Rp. 1,956,535, - companies provide wages higher than the minimum wage of Rp. 2.000.000, - higher.It can be concluded that the imposition of a pay system based on hours worked by the employee obtained the greater number of hours of work, the higher the income the salary received by the employee PT.Thiess Contractor Indonesia